Теоретичні засади проблеми формування комп'ютерної залежності серед дітей та підлітків - Мартинюк, Тетяна Анатоліївна; Martyniuk, Tetiana A. (Чернігівський національний педагогічний університет імені Т. Г. Шевченка., 2014)
Стаття присвячена теоретичному аналізу основних наукових підходів щодо особливостей виникнення залежності від комп’ютера. Вказано чинники та провідні мотиви, що сприяють дормуванню данного виду залежності. Висловлено припущення, що чинники виникнення комп'ютерної залежності можуть одночасно бути чинниками захисту від виникнення данного виду залежності. In the article the problem of computer dependence prevention is examined as one of the tasks of social pedagogy. The article highlights the issue of computer dependence in youth. The author analyzes scientific approaches to the interpretation of the concepts of the computer dependence, the computer addiction. Computer addiction includes Internet addiction, computer games addiction. The author emphasizes that computer addiction is not formed due to prolonged computer work, but only if the action of specific factors.
The theoretical basis of the problem of the formation of computer dependence among of children and youth
Keywords: залежність від комп'ютера; комп'ютерна адикція; педліткові реакції; чинники; мотиви; dependence on a computer; addictive behaviour; pedagogical prevention; computer addiction; teenager; socially-pedagogical conditions